2000
DOI: 10.1063/1.373224
|View full text |Cite
|
Sign up to set email alerts
|

Precise noise characterization of perpendicular recording media

Abstract: Perpendicular recording is one of the technology candidates to extend the areal density growth trend with the superior thermal stability and the high recording resolution. As we have experienced with longitudinal recording, noise originating from perpendicular recording also has a strong impact on the channel performance. In this study, the noise characteristics of the readout waveforms of a tri-layer perpendicular media and single-pole write/MR read heads were investigated using precise time-domain analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Transition jitter noise [5,6] becomes a serious problem because grain size reduction is limited. A percolated perpendicular medium (PPM) has been proposed to increase the resolution of the signal without sacrificing thermal stability [7].…”
Section: Introductionmentioning
confidence: 99%
“…Transition jitter noise [5,6] becomes a serious problem because grain size reduction is limited. A percolated perpendicular medium (PPM) has been proposed to increase the resolution of the signal without sacrificing thermal stability [7].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic feature of CoCrPt-SiO 2 granular perpendicular medium (GPM) is its improved recording density with higher thermal stability and better recording resolution. However, the area density of CoCrPt-SiO 2 GPM cannot be increased arbitrarily; it is observed that the area density above 500 Gb/in 2 causes thermal instability and increased transition jitter noise [5][6][7]. In order to further increase the area recording density, the magnetic grain size must be further scaled down to less than 7 nm to reduce transition jitter noise while simultaneously maintaining a sufficient medium signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we revealed that transition jitter noise is dominant and is determined by magnetic cluster size in perpendicular magnetic recording [1,2]. Then we used Voronoi cells in order to express magnetic grain size or magnetic cluster size.…”
Section: Introductionmentioning
confidence: 99%